Standarisasi penilik jemaat (penatua) menurut 1 Timotius 3 - Nehemia Pasaribu (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
1 Timothy 3 is a guide given by the Apostle Paul to Timothy regarding the criteria that must be possessed by a church overseer or elder in the church. This standardization covers various aspects of character, morality, and ability that aim to ensure that church leaders have the integrity and capacity needed to lead the congregation well. The standard is that a church overseer must have good character, be able to be a leader at home, have good morals, have spiritual maturity, and be responsible in service. The purpose of the discussion that the researcher describes is to maintain the purity of the teachings and life of the church, and to ensure that the congregation is led by individuals who are faithful, wise, and trustworthy. This study uses a qualitative method by collecting data from scientific papers that lead to the object of research. The results that can be presented are that through this standardization, the church can have a strong basis for the selection and development of church leaders, as well as strengthening the structure and quality of leadership in the Christian church. Thus, this study contributes to a better understanding of church leadership standards that are in accordance with biblical principles.